Safety and efficacy of subretinal readministration of a viral vector in large animals to treat congenital blindness - Amado, Defne; Mingozzi, Federico; Hui, Daniel; Bennicelli, Jeannette L; Wei, Zhangyong; Chen, Yifeng; Bote, Erin; Grant, Rebecca L; Golden, Jeffrey A; Narfstrom, Kristina; Syed, Nasreen A; Orlin, Stephen E; et al. (Science translational medicine, 2010)
Leber's congenital amaurosis (LCA) is a group of severe inherited retinal degenerations that are symptomatic in infancy and lead to total blindness in adulthood. Recent clinical trials using recombinant adeno-associated virus serotype 2 (rAAV2) successfully reversed blindness in patients with LCA caused by RPE65 mutations after one subretinal injection. However, it was unclear whether treatment of the second eye in the same manner would be safe and efficacious, given the potential for a complicating immune response after the first injection. Here, we evaluated the immunological and functional consequences of readministration of rAAV2-hRPE65v2 to the contralateral eye using large animal models. Neither RPE65-mutant (affected; RPE65(-/-)) nor unaffected animals developed antibodies against the transgene product, but all developed neutralizing antibodies against the AAV2 capsid in sera and intraocular fluid after subretinal injection. Cell-mediated immune responses were benign, with only 1 of 10 animals in the study developing a persistent T cell immune response to AAV2, a response that was mediated by CD4(+) T cells. Sequential bilateral injection caused minimal inflammation and improved visual function in affected animals. Thus, subretinal readministration of rAAV2 in animals is safe and effective, even in the setting of preexisting immunity to the vector, a parameter that has been used to exclude patients from gene therapy trials.